A Small-Scale Farming Intervention Plan for Inclusive Economic Development in Rural South Africa - Mike Muzekenyi; Farai Nyika; Muhammad Hoque (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Small-scale commercial farming firms play a critical role in achieving the objectives of the African Union’s Agenda 2063, and the United Nations Sustainable Development Goals (SDGs) in the rural economies of Sub-Saharan Africa. South Africa has a sizeable number of households engaged in small-scale agriculture to supply rural market demand. Small scale commercial agriculture has become a key source of revenue, employment, and food security for communities in rural areas. As such, the South African government has been assisting small-scale farmers financially via the Micro-Agriculture Finance Institutions of South Africa and the Department of Agriculture, Forestry, and Fisheries. This support aims to alleviate poverty, create jobs, and improve food security by promoting small-scale commercial farming, primarily in rural areas. Despite this assistance, there is no clear strategy for achieving significant and evidence-based development. This study outlines a four-step intervention strategy for promoting small-scale commercial farming as a strategy for rural economic development in South Africa. These steps include defining a small-scale farming development strategy, and delineating production, performance, policy, and control measures.